Hyperreactio luteinalis and hypothyroidism: A case report - Alejandro Pérez Chaverri; Beatriz Elizabeth Aguilar Solis; Félix Domínguez Paulín; José Eugenio Guerra Cárdenas (Elsevier, 2019)
We report a case of hyperreactio luteinalis (HL) and hypothyroidism diagnosed at 13 weeks of pregnancy. A 29-year-old woman with a spontaneous 13-week singleton pregnancy presented with hirsutism and a pelvic mass. Ultrasound showed a viable pregnancy compatible with the gestational age and multiple cystic lesions on both ovaries. Her TSH levels were markedly elevated and diagnostic of hypothyroidism, for which she was treated. Two days after presentation, she had a spontaneous abortion. The products of conception were histologically normal. Follow-up at 3 months showed resolution of the ovarian cysts, and the previously elevated androgen levels were in the normal range. Hyperreactio luteinalis was diagnosed. Her elevated TSH levels may have contributed to hyperreactio luteinalis through the activation of the hCG receptor. Keywords: Hyperreactio Luteinalis, Hypothyroidism, Pregnancy